The clues are in the flow: how swim propulsion should be interpreted - Soh, J.; Sanders, R. (Sports Biomechanics, 2021)
The aim of this study was to provide a fundamental understanding of how the hands create swim propulsion by applying Newton's Laws to observations of the behaviour of water in simple demonstrations. Using a video recorder, we captured a series of straight and curved pulls made near and under the pool surface. The pulls were performed using a plastic disc or a human hand/arm. Videos from the demonstrations showed that masses of water accelerate from the dorsal side of the hand/plastic disc, and in a straight pull, generates a reaction force moving the body forward, consistent with Newton's Laws. Demonstrations conducted on the curvilinear pull indicated that changes in the pull direction result in an interaction with the water to accelerate water backwards to generate a force thrusting the body forward.